Critical issues in global sport management - Schulenkorf, Nico; Frawley, Stephen 1969- (London Routledge, Taylor & Francis Group, 2017)
The social, cultural and economic significance of sport has never been more evident than it is today. Adopting a critical management perspective, this book examines the most important themes and challenges in global sport management. From match-fixing, doping, bribery and corruption to corporate social responsibility, governance, and new media, it helps students, researchers and practitioners to understand the changing face of the global sport industry. Written by leading international sport management experts, Critical Issues in Global Sport Management includes twenty chapters and real-life case studies from around the world. It examines contemporary governance and management issues as well as the ethical challenges faced by the global sport industry, including questions of integrity and accountability in recent drug scandals that have been widely reported and debated. This book deals with such questions and many more, highlighting the fact that the global sport system is in urgent need of new and innovative solutions to these ongoing problems.
Critical issues in global sport / Nico Schulenkorf and Stephen Frawley -- Part 1 : Governance, integrity and welfare. Governance, CSR and diversity : a critical field of study in global sport management / Johanna A. Adriaanse, Sarah Cobourn and Stephen Frawley -- Gender diversity in the governance of international sport federations / Johanna A. Adriaanse -- Integrity and corruption in sport / Catherine Ordway and Hayden Opie -- Match-fixing and manipulation in sport / Markus Breuer and Sebastian Kaiser -- Doping control and global sport / Jules R. Woolf -- Head injuries and concussion issues / Annette Greenhow and Lisa Gorthorp -- Part 2 : Globalisation. Globalisation and professional sport / Geoff Dickson and João M.C. Malaia Santos -- Socio-economic impacts of sports mega-events : more unintended than intended? / Wolfram Manzenreiter and John Horne -- Social media, fan engagement and global sport / Olan Scott, Michael Naylor and Katherine Bruffy -- Managing football hooliganism / Joel Rookwood -- Farewell to the hooligan? modern developments in football crowd management / Geoff Pearson and Clifford Stott -- Global sport-for-development / Nico Schulenkorf, Emma Sherry and Katie Rowe -- Sport and international diplomacy / Robert E. Baker and Pamela H. Baker -- Part 3 : Technology and social media. Analytics, technology and high-performance sport / Bill Gerrard -- A general theory of the use of technology in sport and some consequences / Harry Collins and Robert Evans -- The tyranny of perpetual innovation : global mobile media, digital communications and television / Brett Hutchins and David Rowe -- Social media analytics for sport management : pitfalls, tools and best practices / Larena Hoeber and Orland Hoeber -- Digital technology and sport sponsorship / Christopher Rumpf and Christoph Breuer -- Current trends and future research challenges in global sport management / Stephen Frawley and Nico Schulenkorf.
Includes bibliographical references and index.
Keywords: Sports administration; Sports and globalization